IMPLEMENTASI KEBIJAKAN RELOKASI PEDAGANG KAKI LIMA DI KABUPATEN SUMEDANG - Anne friday Safaria; Sri Sumiati; Tintin Karwati (Journal Of Regional Public Administration (JRPA), 2020)
This research aims to see implementations of street vendor relocation policy, constraining factor implementations of street vendor relocation policy, and efforts made to addreses implementation of street vendor relocation policy in Dinas Koperasi, UKM, Perdagangan dan Perindustrian Sumedang District. This research methode uses qualitative descriptive (Naturalistic Setting). The sampling was trough literature and observation (interview and documentation). The sampling in this research using purposive sampling which mean consist of 3 people. While data processing procedures using data analytical model Miles and Huberman consisting of data reduction, data presentation, and verification. The result of this research conclude that implementations of street vendor relocation policy Dinas Koperasi, UKM, Perdagangan dan Perindustrian Sumedang District has been going well but not maximally. It’s indicated by phenomena of (1) there’s too much illegal street vendor (2) too much street vendor in sidewalk (3) low awareness against government regulations (4) lack of obdience to government policies. The suggestions for this research is do more socialization with street vendor, cooperate with tenant relation, giving specification tasks, and carry out stricted supervision which mean the goals of policy can be achived.